Inhibitory and facilitatory connectivity from ventral premotor to primary motor cortex in healthy humans at rest – A bifocal TMS study - Bäumer, T.; Schippling, S.; Kroeger, J.; Zittel, S.; Koch, G.; Thomalla, G.; Rothwell, J.C.; Siebner, H.R.; Orth, M.; Münchau, A. (Clinical neurophysiology, 2009)
In macaques, intracortical electrical stimulation of ventral premotor cortex (PMv) can modulate ipsilateral primary motor cortex (M1) excitability at short interstimulus intervals (ISIs). Adopting the same conditioning-test approach, we used bifocal transcranial magnetic stimulation (TMS) to examine intrahemispheric connectivity between left PMv and M1 in humans. A conditioning stimulus (CS) was applied to PMv at intensities of 80% and 90% of active motor threshold (AMT) and 90% and 110% of resting motor threshold (RMT). A supra-threshold test stimulus (TS) was given 2, 4, 6, 8 and 10 ms after the CS and the amplitude of the motor evoked potential (MEP) was measured to probe corticospinal excitability. The CS facilitated corticospinal excitability in ipsilateral M1 when PMv was stimulated with 80% AMT 4 or 6 ms before the TS. At the same ISIs, the CS suppressed corticospinal excitability when the stimulus intensity was increased to 90% RMT. Conditioning effects were site-specific because conditioning the dorsal premotor cortex (PMd) at three different sites produced different effects. Using neuronavigated TMS the PMv site where applied CS produced changes in ipsilateral M1 excitability was located at the border between ventral Brodmann area (BA) 6 and BA 44, the human homologue of monkey’s PMv (area F5). We infer that the corticospinal motor output from M1 to contralateral hand muscles can be facilitated or inhibited by a CS over ipsilateral PMv. The fact that conditioning effects following PMd stimulation differ from those after PMv stimulation supports the concept that inputs from premotor cortices to M1 are functionally segregated.